2021
DOI: 10.1108/ijm-04-2021-0240
|View full text |Cite
|
Sign up to set email alerts
|

Investigating training effectiveness of public and private banks employees in this digital age: an empirical study

Abstract: PurposeThe purpose of this study is to examine the pre-training and post-training variables influencing employee training effectiveness in the banking industry in this era of the digital age.Design/methodology/approachThis study adopted a cross-sectional research design and a structured questionnaire to survey the participants (i.e., bank employees) (n = 702) for data collection. The data gathered from the surveyed respondents were analyzed using the Partial Least Square to Structural Equation Modeling (PLS-SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 126 publications
0
15
0
2
Order By: Relevance
“…The bank is a highly regulated financial institution incorporated with the economy's high social value systems and monetary regulatory authority (Akther and Rahman, 2021). In Indonesia, the implementation of Bank Indonesia (BI) tasks in the monetary, banking and payment system sectors is supported by the internal management sector, continuously developing and improving.…”
Section: Introductionmentioning
confidence: 99%
“…The bank is a highly regulated financial institution incorporated with the economy's high social value systems and monetary regulatory authority (Akther and Rahman, 2021). In Indonesia, the implementation of Bank Indonesia (BI) tasks in the monetary, banking and payment system sectors is supported by the internal management sector, continuously developing and improving.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in IT have changed the conventional ways of delivering service in firms, and in financial institutions such as banks (Raza et al., 2020). A bank is a highly regulated financial institution, incorporated in the economy's social value systems, and a monetary and regulatory authority (Akther & Rahman, 2021). In Indonesia, the Bank Indonesia is tasked with the monetary banking and payment systems and, supported by internal management, with continuously developing, and improving.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the significance of employee performance on profitability and on long‐term organizational success, banks require specialized, skilled, and compassionate employees to sustain success (Akther & Rahman, 2021). Studies have suggested that, on average, employees spend one to 2 hours every weekday, while they are at work, using IT devices connected to the internet for non‐work‐related purposes (i.e., cyberloafing) (Kim, 2018), accounting for 10%–30% of their work time (Agarwal, 2019; Askew et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Good training management encourages improved information about its content, methods, and quality of trainers. It also promotes the motivation of training participants, which results in training effectiveness [57][58][59]. Preparation before training, which is part of its management, can encourage the increased motivation of participants to create training effectiveness [60][61][62].…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%